Deporte de la Polonia de la “cortina de hierro” (2022)
The purpose of the article is to describe the Poland behind the “iron curtain” and the relationship between political regime and sport. Understanding how Poland was formed and how it developed politically is important for the reader to understand how this country dealt with high performance sport during the “iron curtain” period. Sport spread in the Kingdom of Poland through Sokol, being founded in 1867. In this country, certain games were created that became the cultural heritage of this nation. These modalities were pieklo and niebo, sztekiel, stock, piersaeniówka and kulotko. Since 1947, Poland adopted the political regime of the Union of Soviet Socialist Republics (USSR) and applied the Soviet sports system to its population. Young people started practicing sports at school when they were children and were accompanied until they reached adulthood. In conclusion, Polish sport achieved competitive success because it followed the scientific methodology of sports training of the USSR.